Dramaturgi Panggung Depan Terdakwa Ferdy Sambo - Gabirel Langga (Jurnal Komunikasi Nusantara, 2023)
The courtroom is one of the communication contexts of the defendant Ferdy Sambo. The purpose of this study is to explain the communication of the defendant Ferdy Sambo in the South Jakarta District Court using Goffman's approach. This research is qualitative in nature and the method used in this research is the interpretive qualitative paradigm. Researchers used research objects and subjects in the trial of the Joshua murder case and the communication behavior of the defendant Ferdy Sambo at the South Jakarta District Court. The data used in this study consisted of primary and secondary data. The main information of this research was obtained by conducting direct observation as research material on the broadcast of the testimony of the defendant Freddy Sambo on television media. However, other sources of information that are the material of this research are literatures that support this research. This research reveals that the South Jakarta District Court courtroom is a space of verbal and non-verbal communication, where the defendant Ferdy Sambo avoided the death penalty. The defendant Ferdy Sambo used verbal and non-verbal communication as his strategy to gain sympathy from law enforcement so that his sentence was commuted by the judge in the case of Brigadier Joshua. Communication of the defendant Ferdy Sambo in managing impressions by presenting the front stage as a consideration in the decision in the case. Abstrak Ruang sidang merupakan salah satu konteks komunikasi terdakwa Ferdy Sambo. Tujuan dari penelitian ini adalah untuk menjelaskan komunikasi terdakwa Ferdy Sambo di Pengadilan Negeri Jakarta Selatan dengan menggunakan pendekatan Goffman. Penelitian ini bersifat kualitatif dan metode yang digunakan dalam penelitian ini adalah paradigma kualitatif interpretif. Penelitian ini menggunakan objek penelitian dan subjek dalam persidangan kasus pembunuhan Joshua dan perilaku komunikasi terdakwa Ferdy Sambo di Pengadilan Negeri Jakarta Selatan. Data yang digunakan dalam penelitian ini terdiri dari data primer dan sekunder. Informasi utama penelitian ini diperoleh dengan melakukan observasi langsung sebagai bahan penelitian terhadap tayangan kesaksian terdakwa Freddy Sambo di media televisi. Namun, sumber informasi lain yang menjadi bahan penelitian ini adalah literatur-literatur yang mendukung penelitian ini. Penelitian ini mengungkapkan bahwa ruang sidang Pengadilan Negeri Jakarta Selatan merupakan ruang komunikasi verbal dan non-verbal, di mana terdakwa Ferdy Sambo terhindar dari hukuman mati. Terdakwa Ferdy Sambo menggunakan komunikasi verbal dan nonverbal sebagai strateginya untuk mendapatkan simpati dari penegak hukum agar hukumannya diringankan oleh hakim dalam kasus Briptu Joshua. Komunikasi terdakwa Ferdy Sambo dalam pengelolaan kesan dengan menampilkan panggung depan sebagai pertimbangan dalam putusan dalam perkara.